If i stay ebook - Forman, Gayle (If I Stay, 2009)
Heart-wrenchingly raw and heartbreakingly romantic, Gayle Forman’s international bestseller asks the ultimate question: What would you do if you had to choose? “Beautifully written.”— Entertainment Weekly “Every moment I spent reading Forman’s masterpiece drew me in more.”—NPR.com Everything can change in an instant. For Mia, the day started like any other, surrounded by a loving family, an adoring boyfriend, and a bright future filled with music and infinite possibilities. What she never expected is the choice before her now. Caught between life and death, between a happy past and an uncertain future, Mia has to contemplate everything she holds dear and make a choice: to go or to stay.  Adapted into a major motion picture starring Chloe Grace Moretz, Mia's story will stay with you for a long, long time.